SMART DRUG DISTRIBUTION SYSTEM - DR SUMIT SINGH PHUKELA; Dr Omkar Shetty; Dr. Surbhi Priyadarshi; Yash Singh; Juhi Ruth Sinha; Sakshi Gupta (The Bioscan, 2025)
Currently, there is no fully automated medicine-dispensing machine available in the market, making this innovation the first of its kind. Literature shows that courts have penalized doctors for illegible handwriting on prescriptions. A doctor’s prescription is not only a guide for patients but also an instruction manual for family members, a document for chemists to dispense correct medications, and an important medical record for other healthcare providers. Illegible prescriptions can lead to misinterpretation, loss of information, and compromised patient care. The solution lies in digitizing the process of prescription generation and dispensing. The proposed automated medicine-dispensing machine aims to solve these challenges by enabling accurate, secure, and efficient distribution of commonly prescribed medicines in dentistry.